Fat-adaptation strategies for endurance performance: A brief review - Burke, L. M.; Hawley, J. (International SportMed Journal, 2002)
Endogenous fat stores provide fuel for exercise, and training enhances the muscle`s capacity to oxidize these stores. Increasing fat utilization during exercise can spare muscle glycogen use and thus enhance endurance and performance. A 1- to 3-day high-fat, low-carbohydrate diet impairs performance because it depletes muscle glycogen stores without significantly changing fat utilization. Athletes who undertake such a diet for longer periods (as little as 5-6 days) adapt by increasing fat oxidation during exercise. In this fat-adapted, carbohydrate-restored condition, prolonged exercise can be undertaken with greater fat utilization and sparing of muscle glycogen use. Despite marked changes in fuel metabolism during submaximal exercise, fat adaptation does not clearly enhance athletic performance. It appears that glycogen sparing is not important for events lasting 2-3 hours when the athlete is able to consume carbohydrate before and during the event. Ultraendurance athletes might benefit from a combination of fat adaptation and carbohydrate intake for events lasting >4 hours, but there appears to be an individual response to this practice.